Efficacy of Sophora japonica L. Pill in Subjective Memory Complaints in Healthy Adults: a protocol of randomized, double-blind, placebo-controlled, parallel-group, clinical trial - Yunna Kim; Seung-Ho Lee; Yerim Jeon; Seung-Hun Cho (Journal of Pharmacopuncture)
Objectives: Subjective memory complaints, increasingly common among older adults, may indicate early cognitive decline or dementia. Sophora japonica L., a herbal medicine in Korean medicine, has shown potential cognitive benefits in preclinical studies through neuroprotective and anti-inflammatory properties. Given limited efficacy of current pharmacological treatments for cognitive impairment and growing interest in natural products, investigating S. japonica extract in humans is warranted.Methods: This randomized, double-blind, placebo-controlled trial will involve 100 participants aged 40-70 years with subjective memory complaints but without diagnosed cognitive impairment. Participants will receive either S. japonica extract (1,250 mg) or placebo daily for 8 weeks. The primary outcome is change in digit span test score, assessing shortterm memory and attention. Secondary outcomes include changes in other cognitive function tests (visual short-term memory, visual learning, and verbal learning), as well as measures of depression (Beck Depression Inventory-II), anxiety (State-Trait Anxiety Inventory- Y), stress (Stress Response Inventory), heart rate variability, and quality of life (EuroQol 5-Dimension-3L). Assessments will be conducted at baseline and after 8 weeks, with safety monitoring throughout the study period.Conclusion: This study will provide evidence on the efficacy and safety of S. japonica extract for improving cognitive function in adults with subjective memory complaints. If proven effective, this supplement could offer a new approach for supporting cognitive health in aging populations. The comprehensive assessment of cognitive, mood, and quality of life outcomes will allow thorough evaluation of its potential benefits.